Analysis of Nairobi International Convention on the Removal of Wrecks 2007 Implementation by Malaysia - Wan Dahalan, Wan Siti Adibah; Cheng, Jia Hiu (Kanun: Jurnal Undang-undang Malaysia, 2025)
The Strait of Malacca is a strait used for international navigation. Although Malaysia is one of the parties to the Nairobi International Convention on the Removal of Wrecks 2007 (Nairobi Convention 2007) for removing shipwrecks in Malaysian waters, however, Malaysian laws on removing shipwrecks are still not sufficient to solve the problems that exist in the Straits of Malacca until now. This is because the removal of shipwrecks is very expensive for the parties involved, and the main problem faced by the Malaysian government is the lack of expenditure. The objective of this study is to analyze the provisions in the Nairobi Convention 2007; to identify how this Convention is implemented into Malaysian domestic law; and identify the problems that exist in the Nairobi Convention 2007 and ways to solve them. Primary sources such as international conventions and Malaysian domestic laws are used in this article. Secondary sources such as library research, website research are also important to obtain articles, online books, and newspapers. Through this study, it is foud that the Nairobi Convention 2007 aims to remove shipwrecks that pose dangers to navigation. This Convention was ratified and implemented in Malaysia in 2015 in order to be able to move shipwrecks in the Strait of Malacca, as suggested in a symposium held by the International Maritime Organization. Malaysia cannot heavily rely on the Nairobi Convention 2007 and creating its own uniform regulations for shipwreck removal is important. Appropriate action needs to be taken by Malaysia authorities to implement a comprehensive new law for the removal of shipwrecks in the Strait of Malacca. Keywords: The Strait of Malacca, shipwrecks, Nairobi Convention 2007, Cooperative Mechanism, ratification, UNCLOS 1982 Full text:   PDF